Penerapan Konsep Zero Waste Dalam Perspektif Hukum Lingkungan: Tantangan dan Prospek Masa Depan di Indonesia - Satria Ariayudha Widiatmoko; Adinda Thalia Zahra; Khalisha Nasywa Permana (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
The Zero Waste concept is a comprehensive approach to waste management that aims to minimize waste production from the early stages of the production process to the end of the product life cycle. The basic principles include the application of the 3R concept (Reduce, Reuse, Recycle), as well as the integration of 4R to 5R principles (Reduce, Reuse, Recycle, Replace, and Replant), which emphasize reduction, reuse, recycling, replacement with environmentally friendly goods, and replanting. By implementing a Zero Waste approach, Indonesia has the potential to reduce the impact of environmental pollution, save natural resources, and encourage more responsible consumption patterns. However, the challenge of implementing Zero Waste in Indonesia requires collaboration between the government, private sector, civil society and international institutions to create an environment that supports Zero Waste adoption.